ANALISIS BUTIR SOAL DAN KUALITAS TES - Emrida Harahap; Marnis Khairati Hasibuan; Rahmat Saleh Rangkuti; Syafnan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Item analysis is an essential step in educational evaluation to ensure the quality of test instruments used to measure students' learning outcomes. This study aims to examine the concept of item analysis and test quality as a foundation for developing valid, reliable, and objective evaluation instruments. The research employed a library research method with a qualitative descriptive approach. Data were collected from various literature sources, including books, scientific journals, and research findings relevant to item analysis and educational evaluation. The collected data were then analyzed using content analysis techniques. The findings indicate that item analysis plays a significant role in identifying the quality of each test item through validity, reliability, and difficulty level testing. A high-quality test should meet the criteria of validity, reliability, objectivity, balanced difficulty levels, good discrimination power, and practicality in its application. By conducting systematic item analysis, teachers can improve the quality of evaluation instruments, resulting in more accurate, fair, and trustworthy assessment outcomes. Therefore, item analysis should be carried out continuously to support the improvement of learning quality and the effectiveness of student assessment results.